Effect of Intraoperative Dexmedetomidine Dose on Postoperative First Night Sleep Quality in Elderly Surgery Patients: A Retrospective Study With Propensity Score-Matched Analysis - Cai, Jingjing; Chen, Yuanjing; Hao, Xuechao; Zhu, Xiwen; Tang, Yaxing; Wang, Sheng; Zhu, Tao (Frontiers in Medicine, 2020)
Background: Postoperative sleep disorder is common in elderly surgery patients, and it often worsens their recovery after surgery. This study aimed to explore the effect of intraoperative dexmedetomidine dose on postoperative sleep quality. Methods: Based on information regarding dexmedetomidine use during surgery from an electronic medical record system, 4,349 elderly surgery patients were divided into three groups: 1,374 without intraoperative use of dexmedetomidine (Non-DEX), 917 with dexmedetomidine 0.1–0.2 μg/kg/h (Low-DEX), and 2,058 with dexmedetomidine >0.2 μg/kg/h (High-DEX). The numerical rating scale (NRS) for sleep disturbance during the first night after surgery was recorded, and the incidence of NRS ≥ 6 was considered the primary outcome. Results: NRS (P < 0.001) and incidence of severe sleep disturbance (P < 0.001) were lower in patients receiving intraoperative dexmedetomidine than in those without the intraoperative use of dexmedetomidine. Patients in the Low-DEX group had the lowest incidence, followed by those in the High-DEX and Non-DEX groups (6.7% vs. 13.7% vs. 19.5%). After propensity score matching, 906 pairs of elderly surgery patients were included in the Low-DEX and High-DEX groups, and the Low-DEX group had lower NRS (2.7 ± 2.1 vs. 3.1 ± 2.4, P < 0.001) than the High-DEX group. The incidence of severe sleep disturbance was lower in the Low-DEX group than in the High-DEX group (6.6% vs. 12.8%) with an odds rate of 0.48 (95% confidence interval, 0.35 to 0.67). Conclusions: For elderly patients, intraoperative dexmedetomidine use can significantly improve the quality of the first night sleep after surgery. Low-dose (0.1–0.2 μg/kg/h) dexmedetomidine can have an improvement effect on sleep quality, and it is recommended to improve the quality of postoperative sleep.